2011
DOI: 10.1016/j.juro.2011.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Regional Collaboration to Improve Radiographic Staging Practices Among Men With Early Stage Prostate Cancer

Abstract: Following collaborative feedback on baseline use and review of clinical guidelines, urologists in Urological Surgery Quality Collaborative practices dramatically reduced variations in practice patterns and improved adherence with recommended staging practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 13 publications
1
50
0
Order By: Relevance
“…Guideline adherence for radiographic staging of men with newly diagnosed PCa [133] Implementation of novel clinical pathways to address fluoroquinolone resistance and infectionrelated hospitalizations among men undergoing prostate biopsy [134] Implementation of performance feedback and collaborative-wide educational activities to improve documentation of clinical TNM stage in PCa patients [135] Variation in the use of active surveillance for men with low-risk PCa [ Contemporary patterns of care for men newly diagnosed with PCa [42] Positive surgical margins: rate, contributing factors and rate of additional therapy [43] Active surveillance patterns of care in a contemporary PCa registry [44] RP = radical prostatectomy; ADT = androgen deprivation therapy; EAU = European Association of Urology; CAPRA = Cancer of the Prostate Risk Assessment; PSA = prostate-specific antigen.…”
Section: Caesar: Comparative Effectivenessmentioning
confidence: 99%
“…Guideline adherence for radiographic staging of men with newly diagnosed PCa [133] Implementation of novel clinical pathways to address fluoroquinolone resistance and infectionrelated hospitalizations among men undergoing prostate biopsy [134] Implementation of performance feedback and collaborative-wide educational activities to improve documentation of clinical TNM stage in PCa patients [135] Variation in the use of active surveillance for men with low-risk PCa [ Contemporary patterns of care for men newly diagnosed with PCa [42] Positive surgical margins: rate, contributing factors and rate of additional therapy [43] Active surveillance patterns of care in a contemporary PCa registry [44] RP = radical prostatectomy; ADT = androgen deprivation therapy; EAU = European Association of Urology; CAPRA = Cancer of the Prostate Risk Assessment; PSA = prostate-specific antigen.…”
Section: Caesar: Comparative Effectivenessmentioning
confidence: 99%
“…For example, a recent study showed that when physicians reviewed imaging guidelines for newly diagnosed PC, they engaged in practice patterns more closely aligned to those guidelines. 18 Hopefully studies such as this that highlight the current state of M0 CRPC imaging patterns will spur interest in developing imaging guidelines in men with M0 CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…Physician-led collaboration in genitourinary cancers has demonstrated the ability to inform observational findings from administrative data sets, improve quality, and optimize utilization. [38][39][40] Similarly, the hematuria risk index developed within Kaiser Permanente is progress towards evidence-based determination of the appropriateness of a hematuria evaluation based on individualized risk. 41 Whether payment reform will enhance efforts to target hematuria evaluations to those at highest risk for significant pathology remains to be seen.…”
Section: Discussionmentioning
confidence: 99%